Master or Servant? Agency Slack and the Politics of IMF Lending - Copelovitch, Mark S. (My University, 2007)
This paper argues that states and International Monetary Fund bureaucrats exercise partial but incomplete control over the fund’s lending policies. Using an original dataset of IMF lending to 47 countries from 1984-2003, the author finds that "agency slack," or the extent of staff autonomy, is conditional on the intensity and heterogeneity of preferences among the IMF’s largest shareholder countries.